Swatantrata senaniyo ke yado ke jharokhe (New Delhi Publication Division, Ministry of Information and Broadcasting, GOI, 2020)
This book offers a poignant glimpse into the trials, tribulations, triumphs, sorrows, and joys experienced by freedom fighters during their arduous struggle for independence. It compiles the memoirs of fifty-one freedom fighters who were still alive at the dawn of the twenty-first century. Through their firsthand accounts, the book aims to instill in the younger generation a profound appreciation for the sacrifices made to secure our hard-won freedom.
Keywords: History-India; Memories -Indian Freedom Movement